Immunomodulatory Activity of Allium sativum, Curcuma mangga, and Acorus calamus Combination Nanoparticle on Mice Leukocytes Profile - Bayyinatul Muchtaromah; Nur Izzah Analisa; Mujahidin Ahmad; Prilya Dewi Fitriasari; Soraya Habibi; Alfiah Hayati; Ely Nuril Fajriyah (UIN Sunan Gunung Djati Bandung, 2022)
Immunomodulators are substances acting as stimulants or suppressants against the immune system, either to specific or non-specific activity. The non-specific through the production of leukocytes as the first response in fighting against an attacking antigen. Meanwhile, the specific, hrough recognition of antigens by lymphocytes during reattack. This research aimed to determine the immunomodulatory activity of the extracts combination nanoparticles of Allium sativum, Curcuma mangga, and Acorus calamus on the leukocyte profile of mice. This study used 5 treatments and 6 repetitions. The treatment groups were K- (untreated group), P1 (extracts combination nanoparticle dose of 25 mg/kg), P2 (extracts combination nanoparticle dose of 50 mg / kg), P3 (subur kandungan herbal medicine dose of 75 mg / kg), and P4 (Clomiphene citrate dose of 0.9 mg / kgBW). The parameters used included the total number of leukocytes and their differential value. The data that met the parametric assumptions, such as normally distributed and homogeneous were examined using the One Way ANOVA test, and when there was a significant difference, it was processed with the Duncan assessment. While those that did not meet the assumptions were evaluated using a non-parametric analysis. The statistical results showed that administration of extracts combination nanoparticles of A. sativum, C. mangga, and A. calamus at doses of 25 mg/kg and 50 mg/kg were able to suppress the inflammatory reaction by decreasing the total number of leukocytes. However, the differential leukocyte count was able to maintained or modulate immune system, indicating by the percentage of neutrophil, basophil, and eosinophil in the normal range. At a dose of 50 mg/kg, decreased the percentage of lymphocytes, while for monocytes, all dosage ranges were able to increase their number.